Severe COVID-19 Recovery Is Associated with Timely Acquisition of a Myeloid Cell Immune-Regulatory Phenotype - Trombetta, Amelia C.; Farias, Guilherme B.; Gomes, André M. C.; Godinho-Santos, Ana; Rosmaninho, Pedro; Conceição, Carolina M.; Laia, Joel; Santos, Diana F.; Almeida, Afonso R. M.; Mota, Catarina; Gomes, Andreia; Serrano, Marta; et al. (Frontiers in Immunology, 2021)
After more than one year since the COVID-19 outbreak, patients with severe disease still constitute the bottleneck of the pandemic management. Aberrant inflammatory responses, ranging from cytokine storm to immune-suppression were described in COVID-19 and no treatment was demonstrated to change the prognosis significantly. Therefore, there is an urgent need for understanding the underlying pathogenic mechanisms to guide therapeutic interventions. This study was designed to assess myeloid cell activation and phenotype leading to recovery in patients surviving severe COVID-19. We evaluated longitudinally patients with COVID-19 related respiratory insufficiency, stratified according to the need of intensive care unit admission (ICU, n=11, and No-ICU, n=9), and age and sex matched healthy controls (HCs, n=11), by flow cytometry and a wide array of serum inflammatory/immune-regulatory mediators. All patients featured systemic immune-regulatory myeloid cell phenotype as assessed by both unsupervised and supervised analysis of circulating monocyte and dendritic cell subsets. Specifically, we observed a reduction of CD14lowCD16+ monocytes, and reduced expression of CD80, CD86 and Slan. Moreover, mDCs, pDCs and basophils were significantly reduced, in comparison to healthy subjects. Contemporaneously, both monocytes and DCs showed increased expression of CD163, CD204, CD206 and PD-L1 immune-regulatory markers. The expansion of M2-like monocytes was significantly higher at admission in patients featuring detectable SARS-CoV-2 plasma viral load and it was positively correlated with the levels of specific antibodies. In No-ICU patients, we observed a peak of the alterations at admission and a progressive regression to a phenotype similar to HCs at discharge. Interestingly, in ICU patients, the expression of immuno-suppressive markers progressively increased until discharge. Notably, an increase of M2-like HLA-DRhighPD-L1+ cells in CD14++CD16- monocytes and in dendritic cell subsets was observed at ICU discharge. Furthermore, IFN-γ and IL-12p40 showed a decline over time in ICU patients, while high values of IL1RA and IL-10 were maintained. In conclusion, these results support that timely acquisition of a myeloid cell immune-regulatory phenotype might contribute to recovery in severe systemic SARS-CoV-2 infection and suggest that therapeutic agents favoring an innate immune system regulatory shift may represent the best strategy to be implemented at this stage.